Effect of Brand Image, Celebrity Endorsement, EWOM, Brand Awareness and Social Media Communication on Purchase Intention with Brand Trust as a Mediation Variable on Smartphone Users in Batam City - Golan Hasan; Elviana Elviana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
In this era of globalization, various kinds of products and services are growing and there are also new innovations. Many ways are done by the company to be able to increase the company's turnover and provide good service to consumers in order to satisfy these consumers. With the development of the times, companies must be able to innovate quality products and companies must be able to produce products desired by the community by studying and improving the quality of smartphones continuously. Therefore, the researcher aims to analyze the effect of brand image, celebrity endorsement, ewom, brand awareness and social media communication on purchase intention with brand trust as a mediating variable on smartphone users in Batam City. A total of 400 respondents who can be used in analyzing by using research sampling techniques.